Differentiation of Long Non-Coding RNA and mRNA Expression Profiles in Male and Female Aedes albopictus - Xu, Ye; Dong, Yunqiao; Xu, Yazhou; Lai, Zetian; Jin, Binbin; Hao, Yanqiang; Gao, Yonghui; Sun, Yan; Chen, Xiao-guang; Gu, Jinbao (Frontiers in Genetics, 2019)
The Asia tiger mosquito (Aedes albopictus) is an important vector of arboviruses, and females can transmit pathogens such as the dengue, zika, and chikungunya viruses. Understanding sex-related differences in this mosquito is fundamental for vector control. However, there are no reports of systematic characterization of long non-coding RNAs (lncRNAs) in male and female Ae. albopictus. To investigate the roles of coding and non-coding RNAs in both sexes of Ae. albopictus, RNA sequencing was performed on male and female samples. The results showed 305 differentially expressed protein-coding genes (DEGs) between males and females, of which 198 were highly expressed in males and 125 were highly expressed in females. Sex-associated gene ontology terms were enriched. Analysis with the FEELnc software identified 2623 novel lncRNAs, of which 26 showed male high expression and 11 showed female high expression. Quantitative real-time PCR of randomly selected DEGs and lncRNAs supported the validity of the RNA sequencing results. Knocking down male high-expressed gene AALF000433 in male adults reduced the egg hatching rate. This study provides valuable data on sex-specific expression of protein-coding genes and lncRNAs in adult Ae. albopictus, which will guide further studies aimed at understanding sex development and determination mechanisms in this species.